Interventions for treatment of muscle cramps in hemodialysis patients: A systematic review - Joey Anung Aninditya Widodo; Azizah Khoiriyati (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Background: Physical disorders in patients undergoing hemodialysis therapy are problems that often occur in intradialysis, which if not handled properly will cause discomfort to the patient. Patients suffering from Chronic Renal Failure (CKD) often experience physical suffering and anxiety. Muscle cramps are often associated with hemodialysis side effects. Objective: This systematic review aims to determine interventions that can be used to treat muscle cramps in hemodialysis patients. Method: The research method uses PRISMA with a systematic approach and selection process. Library sources were traced from the ProQuest, Pubmed and Scient Direct databases.  Result: Based on the analysis through systematic review, several interventions can be used to treat muscle cramps in hemodialysis patients, namely isotonic exercise, range of motion, statin therapy. Conclusion: In conclusion, these interventions have an influence on the incidence of muscle cramps experienced by patients with chronic kidney failure during the process of hemodialysis therapy. Abstrak: Latar Belakang: Gangguan fisik pada pasien yang menjalani terapi hemodialisa merupakan masalah yang sering terjadi pada intradialisis, yang jika tidak segera ditangani dengan baik akan menimbulkan rasa tidak nyaman pada pasien. Pasien yang menderita Gagal Ginjal Kronik (GGK) sering merasakan penderitaan fisik dan kecemasan. Kram otot sering dikaitkan dengan efek samping hemodialisa. Tujuan: Systematic review ini bertujuan untuk mengetahui intervensi yang dapat digunakan untuk menangani kram otot pada pasien hemodialisa. Metode : Metode penelitian menggunakan PRISMA dengan pendekatan dan proses seleksi yang sistematis. Sumber pustaka ditelusur dari database ProQuest, Pubmed dan Scient Direct. Hasil: Berdasarkan analisis melalui systematic review didapatkan beberapa intervensi yang dapat digunakan untuk menangani kram otot pada pasien hemodialisa yaitu isotonic exercise, range of motion, statin therapy. Kesimpulan: Kesimpulan intervensi-intervensi tersebut memiliki pengaruh terhadap kejadian kram otot yang dialami pasien gagal ginjal kronik selama proses terapi hemodialisa.